1998
DOI: 10.1097/00005392-199804000-00047
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Significance of False-Negative Sextant Prostate Biopsies

Abstract: Our findings suggest that this 23% incidence of false-negative biopsies represents significant cancer. This relatively high incidence is important to consider in treatment modalities in which prostate biopsy may be performed to determine response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 11 publications
1
85
0
1
Order By: Relevance
“…The above point is more striking when compared with men for whom TTMB was used after two or more earlier negative biopsies (Figure 2c). In these men, the cancer detection rate remained high (38%), but the only areas in which cancer was frequently identified were the anterior-most aspects of the gland (regions 1,8,7,9,17,18,19,24). Presumably, with a large enough number of transrectal cores taken (mean of 37.9 prior cores in men with 3 prior biopsies), cancer closer to the rectum is fairly readily discovered.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The above point is more striking when compared with men for whom TTMB was used after two or more earlier negative biopsies (Figure 2c). In these men, the cancer detection rate remained high (38%), but the only areas in which cancer was frequently identified were the anterior-most aspects of the gland (regions 1,8,7,9,17,18,19,24). Presumably, with a large enough number of transrectal cores taken (mean of 37.9 prior cores in men with 3 prior biopsies), cancer closer to the rectum is fairly readily discovered.…”
Section: Discussionmentioning
confidence: 97%
“…For each biopsy core, the template coordinate and the offset from base were recorded. Biopsy regions included posterior prostate (3,4,12,13,21,22), posterior lateral (2,5,11,14,20,23), anterior lateral (1,6,9,10,15,16), anterior apex (19,24), and TZ (7,8,17,18) After completion of all sampling, patients underwent cystoscopic evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Recently, the average number of biopsies has been gradually increasing, however, the detection rate remains unchanged and the need of repeat biopsy is increasing. Despite the high rate of false negative biopsy findings (20-30%), as reported by Rabbani et al 12 and Fleshner and al. 13 , sextant biopsies are still in wide use.…”
Section: Introductionmentioning
confidence: 83%
“…Studies have shown that in more than 20% of cancers, at least two biopsy sessions were required to diagnose the tumor, and it is not yet clear how many samples (per session) are necessary to reach a diagnosis. Although increasing the number of random TRUS biopsy samples yields a marginal improvement in detection rate [16,9,18], only a very small fraction of the gland is sampled with even a dozen needle placements. Thus, it is unlikely that simply increasing the number of samples taken will solve the problem.…”
Section: Introductionmentioning
confidence: 99%